The amalgam of naive CD4+ T cell transcriptional states is reconfigured by helminth infection to dampen the amplitude of the immune response - Even, Zachary; Meli, Alexandre P.; Tyagi, Antariksh; Vidyarthi, Aurobind; Briggs, Neima; de Kouchkovsky, Dimitri A.; Kong, Yong; Wang, Yaqiu; Waizman, Daniel A.; Rice, Tyler A.; De Kumar, Bony; Wang, Xusheng; et al. (Immunity (Cambridge, Mass.), 2024)
Naive CD4+ T cells in specific pathogen-free (SPF) mice are characterized by transcriptional heterogeneity and subpopulations distinguished by the expression of quiescence, the extracellular matrix (ECM) and cytoskeleton, type I interferon (IFN-I) response, memory-like, and T cell receptor (TCR) activation genes. We demonstrate that this constitutive heterogeneity, including the presence of the IFN-I response cluster, is commensal independent insofar as being identical in germ-free and SPF mice. By contrast, Nippostrongylus brasiliensis infection altered this constitutive heterogeneity. Naive T cell-intrinsic transcriptional changes acquired during helminth infection correlated with and accounted for decreased immunization response to an unrelated antigen. These compositional and functional changes were dependent variables of helminth infection, as they disappeared at the established time point of its clearance in mice. Collectively, our results indicate that the naive T cell pool is subject to dynamic transcriptional changes in response to certain environmental cues, which in turn permutes the magnitude of the immune response. [Display omitted] •Naive CD4+ T cell transcriptional heterogeneity is commensal independent•Helminth infection recasts the basal transcriptional profile•These transient, IL-4-dependent changes correspond to the period of active infection•Helminth-induced changes correlate with suppressed activation of bystander T cells The discovery of naive CD4+ T cell transcriptional heterogeneity raises the question regarding its plasticity and the mechanisms that may perturb the basal state. Even et al. report that, in mice, helminth infection, but not commensal colonization, transiently recasts this amalgam to dampen bystander T cell activation during active disease.